“Magic Boosed” an elementary school geometry textbook with marker-based augmented reality - Reza Andrea; Siti Lailiyah; Fahrul Agus; Ramadiani Ramadiani (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Recently media that is used on mathematic study is just board and printed book. Usually teacher uses, modelling tool to visualize study objects like geometry, but students must be in alternatively to fulfill that demand requires application which can deliver 3-dimension geometry to emphasize students understanding of volume and surface area. This research will implement based tracking marker method on textbook and develop geometry study application based on augmented reality, it is called “Magic Boosed”. The existence of AR combination technology, then geometry which will be taught by teacher to elementary school student will be more interesting and make students are easier to learn shape and geometry formulas, this is evident from data analysis test on student learning improvement using kolmogorov-smirnov testing.